Heterogeneous impairment patterns among midlife Latinos in the United States. - Boen, Courtney E; Parrish, Elise M; García, Catherine; Garcia, Marc A (Journals of Gerontology Series B: Psychological Sciences & Social Sciences, 2026)
Objectives Latinos are a large, growing, and diverse group whose disability and impairment profiles prominently shape patterns of population aging in the United States. To date, however, research has largely documented disability and impairment risks among older Latinos under a pan-ethnic umbrella, with fewer studies investigating disparities among Latino subgroups at midlife working ages. This study aims to estimate population-level impairment prevalence among midlife working-aged Latinos in the United States, paying particular attention to the subgroup heterogeneity. Methods Using data from the American Community Survey (2008–2019) (n  = 1,032,333), we document patterns of impairment—including overall impairment and by impairment type (i.e. cognitive and physical impairments)—among Latinos aged 45–64, examining heterogeneity across nativity and citizenship, age at migration, duration in the United States, heritage and country/region of origin, and race. Taking an intersectional approach, we further consider whether these patterns vary by gender and age. Results Our findings show substantial heterogeneity in impairment among Latinos, with Puerto Rican, American Indian, and Alaska Native, Black, and multiracial Latinos having especially high probabilities of impairment. U.S.-born Latinos, immigrants who migrated as children or adolescents, and those who have resided in the United States for extended durations also experience relatively high probabilities of impairment. Discussion Understanding impairment patterns among Latino subgroups during midlife working ages is crucial for addressing health disparities and promoting health equity within this diverse and growing population. Our findings suggest that not considering within-group diversity among pan-ethnic Latinos risks masking substantial heterogeneity, with important consequences for policy and intervention efforts.